Evaluation of outcome in arc of motion of elbow after arthrolysis in post-traumatic stiff elbow through posterior triceps reflecting anconeus pedicle approach - Sai Phanindra Malladi; Pamarthi Srinivas; Raju Byshetty (Asian Journal of Medical Sciences, 2022)
Background: The elbow is a synovial hinge joint, with a high chance of stiffness. A stiff elbow is an elbow with a loss of extension of >30° and flexion of <120 which can result due to post-traumatic events around elbow. Surgical intervention is required if conservative treatment fails. The arthrolysis of the elbow by posterior approach has been reported less widely. Aims and Objectives: This study aims at reporting the arc of motion of the elbow after arthrolysis by posterior approach by TRAP approach. Material and Methods: This study was done on 26 patients with post-traumatic elbow stiffness through posterior triceps reflecting anconeus pedicle graft approach. The mean age of patients in our study is 30.8, ranging from 15 to 54 years. After surgery, patients were reviewed to assess arc of motion and fixed flexion deformity (FFD) improvement, MAYO and oxford score. Results: Our study showed increase in arc of motion from 50.7° to 90.7°, FFD decrease from 31.3° to 18.2° and MAYO score which had a pre-operative mean of 77.3, increased to 90 postoperatively with excellent result in 18 cases (69.2%) and good in eight cases (30.8%). Oxford score had an improvement from 21.8 to 40.3 showing satisfactory result in 11 cases. Conclusion: The approach described in our study is ideal for posterior bony blocks with maintaing intact extensor mechanism and less chance of neurovascular damage. Stability of the joint is maintained with feasability to do ulnar nerve transposition.